Pendugaan Angka Partisipasi Kasar Pendidikan Anak Usia Dini Berdasarkan Jenis Kelamin dan Level Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2022 dengan Pendekatan Model Hierarchical Bayes Berdistribusi Beta dengan Measurement Error - Rodliyah, Ratih; Ubaidillah, Azka (Seminar Nasional Official Statistics, 2023)
Quality education is one of the goals of the 2030 Sustainable Development Goals (SDGs). Services to education can be provided from an early age to prepare for further formal education. Susenas produced an estimator of the Gross Enrollment Rate (APK) for Early Childhood Education (PAUD) to describe the capacity of the country's education system to accommodate students in the early age group. Small area statistics urgently needed to create policies that are more right on target. Central Java province has APK PAUD based on sex which is still inadequate for all districts/cities based on the Relative Standard Error (RSE). Therefore, this study applies indirect estimation to improve the precision of the direct estimator using Small Area Estimation (SAE) with measurement error (ME) using Hierarchical Bayes (HB) Normal distribution and Hierarchical Bayes (HB) Beta distribution. The results of this study indicate that the estimated value using the HB ME Beta method is more precise than direct estimation and SAE HB ME Norm estimation.